Delocalized Ag−Ag dimer rattling mode contributes to reduced thermal conductivity and enhanced thermoelectric performance in AgAs2 - Jie Zhang; Minghao Zhan; Wending Wang; Xiaohong Xia; Yun Gao; Zhongbing Huang (Results in Physics)
Layered thermoelectric materials inherently feature a decoupling of electron and phonon transport, attributed to the high electrical conductivity within the covalent atomic layers and the increased phonon scattering at the layer boundaries. However, the weak atomic interactions along the out-of-plane direction present a considerable obstacle in enhancing the thermoelectric performance of these materials. In this work, we employ RuAs4 (FeAs4), SrAs4 (CaAs4), and AgAs2 (CuAs2) as representative compounds to theoretically explore the influence of bonding characteristics on the carrier transport in quasi-layered structures. We find that, in comparison to RuAs4 (FeAs4) with a similar atomic mass and crystal structure, the room temperature lattice thermal conductivity can be dramatically decreased from 10.2 (5.6) W/mK to 0.83 (1.69) W/mK in SrAs4 (CaAs4). This reduction is linked to the weak ionic interaction between the covalently bonded As layers and the Sr (Ca) atoms, resembling a rattling model that effectively scatters heat-conducting acoustic phonons. Conversely, the subvalent Ag2 dimers and delocalized Ag−As bonds in AgAs2 ensure rational electrical transport while preserving significant lattice anharmonicity due to the dimer clusters’ rattler-like behavior. Coupled with an enhanced Seebeck coefficient resulting from the elevated valence band degeneracy, we predict an p-type average thermoelectric ZT of 2.8 at 400 K. Our results provide an approach for modulating carrier transport in layered thermoelectrics via atomic or cluster intercalation, potentially serving as a guide for identifying novel thermoelectric materials.